Influencia de la narrativa hipermedia en los medios digitales: caso decreto 883 - Alarcón Roos, Nicole Jamiléth (2020)
The digital generation has caused a great impact on people's lives despite its relatively recent appearance. In the daily newspaper, the great importance of digital media for the development of human interaction is seen. For this reason, this research collects data that support the level of influence that digital media can have on people, reaching a shock in different ways to produce social conflicts. For the collection of these data, direct observation, interview and survey were used, three research techniques that give more support to the results obtained. In this way it was possible to verify that the digital media does influence a society, either negatively or positively, and in some cases its influence is higher and in other cases a little reduced, it can still be shown that the contents that propagate by these means can easily move masses, as in the case of the October of 2019, in Ecuador by Decree 883 where digital media were a great communication tool during the development of the conflict. For this reason, it is proposed to encourage the creation of content using reliable sources, finally to encourage the analysis and interpretation of the information we find in these media.